Analysis of the Performance of the Regional Representative Council (DPRD) of Bangli Regency Period 2019 - 2024 - I Nyoman Budiada; I Made Sumada; Ida Ayu Putu Sri Widnyani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The Regional People's Representative Council (DPRD) has the same position as the Regional Government in building and facilitating support in the formulation of regional government policies, which can accommodate and channel the aspirations of the community so that they can be well received. However, in reality, the DPRD has not fully been able to perform its functions well, and in practice, it often blurs the meaning of democracy itself. The implementation of regional autonomy by the Regional Government and DPRD must be carried out according to their respective functions. The DPRD is required to maximize its legislative function to accommodate all aspirations of the people and to prosper the local community, which is the DPRD's obligation. The implementation of the legislative function must be followed up with regional regulations, in this case, in accordance with the Regulations of the Bangli District DPRD No. 1 of 2020 concerning the Rules of Procedure of the Bangli District DPRD, which outline the functions of the DPRD. This research employs a qualitative approach and was conducted at the Bangli District Regional People's Representative Council located on JL. Brigjen Ngurah Rai, Bangli. The results of this study indicate that during the period of 2019-2024, the Bangli District DPRD has not yet shown a number of achievements that deserve appreciation or has not yet optimally fulfilled its role as a representative institution. In terms of the formation of laws and regional regulations, the Bangli DPRD has not successfully produced a series of policies that were planned within annual targets, although the policies or regional regulations that have been established reflect the commitment of the DPRD in responding to the needs and aspirations of the local community. Efforts to improve the performance of the Bangli District DPRD during the period of 2019-2024 in implementing regional autonomy in Bangli District include training, developing oversight strategies, appointing Expert Groups and Advisory Teams, and approving the rules of procedure of the Bangli District DPRD